AB1229-HPR Evaluation of rheumatology nurse-led clinic in managing patients with rheumatoid arthritis: a retrospective study. (15th June 2017) - Leung, YME; Wong, KY; Tam, LS
Abstract : Background: Rheumatoid arthritis (RA) is a chronic, systemic, autoimmune disease characterized by inflammation of the synovial joints. Management of RA patients are usually provided by rheumatologists only. Enhanced care provided by rheumatology nurses between rheumatologist consultations may have beneficial effects in terms of symptom control. In Hong Kong, whether rheumatology nurse care model can favor to patient outcomes remained uncertain. Objectives: The aim of the study was to examine the clinical effectiveness of rheumatology nurse clinic in controlling disease activity as expressed in change of Disease Activity Score in 28 joints in RA patients compared with usual care led by rheumatologists only. Methods: This was a retrospective study. Two historical groups of RA patients (30 patients at each group) were identified from attendance records between 1/1/2015 and 20/7/2015 at the rheumatology outpatient clinics. Group 1 comprised of patients who attended rheumatology nurse clinic in between the doctor clinic consultations. Patient education delivered by the rheumatology nurse included disease mechanism, treatment aim, pain management and checking medication adherence according to prescription. RA treatment could also be intensified if needed. Group 2 comprised of patients managed by rheumatologists only. Primary outcomes were changes in disease activity at follow-up visit after the doctor clinic and nurse clinic. Results: The mean follow-up duration for the study cohort was 20 weeks (median: 22.5 weeks). Patient global assessment and DAS 28 were similar for both groups at baseline. At follow-up, patient global assessment and in the nurse group (Group 1) decreased from mean ± SD: 42±24.7 at baseline to 28.7±24.6 at follow-up, which was approaching the minimal clinically important improvement (MCII= -15). With regards to DAS28, there was a 8.2% decrease (absolute change: -0.38±1.14) in DAS28 in group 1 suggesting a trend of improvement (p=0.081). The corresponding decrease in group 2 was 1.2% (absolute change: -0.05±1.47) and such decrease was not significant (p=0.863). Changes in DAS28 did not exceed minimal clinically important improvement in both groups (MCII= -1.2). Conclusions: This study demonstrates the short-term benefit of a nurse-led program on RA disease management. Future multi-center studies with a randomized controlled design and a larger sample will be required to confirm our findings. Acknowledgements: The author is very grateful to the supervisors from, Professor Wong Kam Yuet, Frances, Hong Kong Polytechnic University; Professor Tam Lai Shan and Dr Zhu Yaner, Tracy the Chinese University of Hong Kong. Lastly, the author would like to thank her parents and friends for their support. Disclosure of Interest: None declared